Appointments, Pay and Performance in UK Boardrooms by Gender. (February 2014) - Gregory‐Smith, Ian; Main, Brian G.M.; O'Reilly, Charles A.
<x xml:space="preserve">Abstract</x> This article uses UK data to examine issues regarding the scarcity of women in boardroom positions. The article examines appointments, pay and any associated productivity effects deriving from increased diversity. Evidence of gender‐bias in the appointment of women as non‐executive directors is found together with mixed evidence of discrimination in wages or fees paid. However, the article finds no support for the argument that gender diverse boards enhance corporate performance. Proposals in favour of greater board diversity may be best structured around the moral value of diversity, rather than with reference to an expectation of improved company performance.